The Women of Get Out: Femininity, Race, and Betrayal in the Contemporary Horror Film. Issue 3 (3rd July 2021) - Greven, David
ABSTRACT: Jordan Peele's horror film Get Out (2017) has been generally acclaimed for its unflinching critique of American racism, made even more notable by the East Coast, liberal-elite setting of the film. While the film commendably organizes its mainstream horror narrative around an African American male protagonist, the film's depiction of femininity has proven controversial. This essay explores the gender politics of the film's depiction of women, especially but not exclusively its White female characters. Drawing on perspectives from psychoanalytic theory, intersectionality, and feminist horror studies, the essay considers the film's reworking of Carol Clover's figure of the "Final Girl" who alone survives the horror movie bloodbath. The function of Peele's Final Girl is less clearly positive, given that this figure is the film's ultimate villain. The essay explores intersections between the film and psychoanalytic attitudes toward female caregivers who fail to conform to gendered standards, theorizing that betrayal emerges as a significantly gendered concept. Get Out unusually depicts maternal loss as a central aspect of its male protagonist's psychology while also foregrounding maternal and other forms of female betrayal.